PHYTOCHEMICAL TEST, TOXICITY TESTS AND ANTIOXIDANT ACTIVITIES OF MAHOGANY SEEDS (Swietenia mahagoni (L) Jacq) - Rindawati, Novi; Daniel, Daniel; Saleh, Chairul (JURNAL ATOMIK, 2019)
Phytochemical tests, toxicity tests and antioxidant activities of mahogany seeds (Swietenia mahagoni (L) Jacq) were carried out. This study is meant to identify the secondary metabolism, the LC50 and LC50 of extract of ethanol, n-hexane fraction, and ethyl acetate fraction with the seeds of (Swietenia mahagoni (L) Jacq). Phytochemical screening on ethanol extract of mahogany seeds showed the presence of alkaloids, flavonoids, triterpenoids and phenolic n-Hexane fraction contains alkaloids compounds, triterpenoid and phenolic compounds. Ethyl acetate fraction contains flavonoids, triterpenoids and phenolic compounds. The toxicity level is performed by tests of BSLT (Brine shrimp lethality test), while antioxidant activity is performed by a spectrofotometr uv-vis. The total extract of ethanol is obtained at the smallest amount of LC50 for 49.47565 ppm, n-Hexane fractions obtained from LC50 as much 75.30347 ppm, ethyl acetate fraction obtained from LC50 as much as 77.87461 ppm and those three extracts are toxic. The IC50 value of a total ethanol of 176 ppm, n-Hexane fraction of as 189 ppm and ethyl acetate fraction of 144 ppm with is strength medium antioxidant.